Digital Shift: An Evaluation of Indonesia’s TV Digitalization Policy Implementation for Low-Income Families - Titania Titania; Hartuti Purnaweni; Dyah Lituhayu; Maryono Maryono (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: The Indonesian Omnibus Law Number 11 of 2020 mandates the transition from analog to digital television through an Analog Switch-Off (ASO) policy, necessitating the provision of set-top boxes (STBs) to facilitate this migration. The effective distribution of STB assistance is a crucial factor for the successful implementation of the ASO policy. Objective: This study aims to evaluate the effectiveness of the Analog Switch-Off (ASO) policy implementation in Depok City by examining the accuracy, timeliness, adequacy, quality, and appropriateness of set-top box (STB) distribution to eligible low-income households. Methods: This research adopts a descriptive qualitative approach to assess the effectiveness of the ASO policy implementation in Depok City, focusing on several dimensions: (1) target accuracy: ensuring that the STBs are distributed to the correct households; (2) timeliness: punctuality in the distribution process; (3) adequacy: sufficient provision of STBs to meet demand; (4) quality: ensuring the STBs meet the required standards; and (5) appropriateness of utilization: confirming that the STBs are used correctly by the beneficiaries. Results: The study reveals that while the STB distribution program has made significant strides, several issues persist. The results suggest that enhanced coordination and support from all involved parties—including government agencies, local authorities, and distribution teams—are necessary to address these issues and improve the overall effectiveness of the program. Conclusion: Strengthening these areas is essential for ensuring that the ASO policy achieves its intended outcomes and benefits low-income households as planned.